INVESTIGATING THE ROLE OF BUILDING INFORMATION MODELING IN RISK MANAGEMENT OF CONSTRUCTION PROJECTS - Abdelalim, Ahmed Mohamed; Elnaggar, Ahmed M. Elshafie (Journal of Civil Engineering, Science and Technology, 2024)
Risk management is a crucial component of building projects that aids in achieving objectives and reducing risks. Risks associated with management, such as coordinating between disciplines and communicating with stakeholders at various project phases, are common in construction projects. This study set out to get a deeper understanding of the ways in which risk management planning methods for building projects might be developed using Building Information Modeling (BIM). A survey instrument was created and dispersed among specialists in the building sector. The questionnaire’s results showed that, despite certain challenges like inadequate training and improper utilization in construction contracts, building information modeling is useful in risk management planning procedures. These challenges could make it impossible for building information modeling to be used in building projects. The majority of respondents did, however, agree that BIM is a useful tool for managing project risk in construction. The study concludes with a conceptual framework for using BIM in risk management procedures across several project life cycles.